A Numerical simulation of emissions of pollutants from industrial chimney - Najim, Saleh I.; Rishack, Qais A.; Mohammed, Alaa H. (Basrah Journal for Engineering Sciences, 2014)
The prediction of the concentration fields of pollutants released to the atmosphere is a key factor in assessing possible environmental damages caused by industrial emissions. To solve the concentration equation for gaseous or particulate effluents it is necessary to know as accurately as possible the velocity field and turbulence intensities at the atmospheric boundary layer in the region of interest. A two dimensional mathematical model based on the equations of fluid mechanics along with a modified non- isotropic k-ε turbulence model are employed to calculate the flow and dispersion at the atmospheric micro scale (distances of the order of kilometers). Results of investigation are obtained by using the finite volume method (FVM) to solve the average Navier Stock equations coupling with turbulent k- ε model. The calculation was carried out for plume flow from the industrial chimney with different plume velocities, wind velocities and heights of stack. The equations of model are solved with SIMPLE schemes. FLUENT program used to show the results of the plume flow at the variable parameters of wind and plume velocities and heights of stack, the code is applied to simulate several cases of flow and dispersion. Comparisons against experimental results show that the non-isotropic turbulence model has better ability to foresee the plume dispersion than the standard k- ε, in which the non-isotropic character of turbulence is relevant. The computational results show that the plume path and concentrations are correctly predicted by the numerical model.